Introduction to the First Special Issue on Pandemics. Issue 3 (September 2021) - Pineo, Ronn
This issue of the Journal of Developing Societies is the first of two special issues addressing key pandemic developments from around the world. This issue focuses on COVID-19, especially looking at the impact on developing societies. The articles analyze events in Nigeria, Zimbabwe, Norway, South Asia, China, and the Philippines.